Promoting a motivational workforce in nursing practice - Karien Jooste (AOSIS, 2003)
The motivation of nurses is a crucial contributing factor to effective health care organisations in South Africa. Opsomming Die motivering van verpleegkundiges is 'n kritiese aangeleentheid wat as bydraend tot effektiewe gesondheidsorgorganisasies in Suid-Afrika gesien kan word. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.